INCIDENCE AND RISK FACTORS FOR ORAL MUCOSITIS AFTER BONE MARROW TRANSPLANTATION PATIENTS UNDER LOW INTENSITY LASER THERAPY: A LONGITUDINAL STUDY - Malta, Cassia Emanuella Nobrega; Rodrigues, Maria Imaculada de Queiroz; Lemos, José Vitor de Mota; Freire, Natalia Costa Bezerra; Duarte, Fernando Barroso; Silva, Paulo Goberlânio de Barros; Alves, Ana Paula Negreiros Nunes (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Bone marrow transplantation (BMT) has been used to treat numerous malignant and non-malignant hematological diseases, genetic and immunological diseases with a high risk of oral mucositis (OM) due to the action of antineoplastic drugs. As photobiomodulation therapy (FBMT) with low-level laser is a proven non-invasive treatment for OM, the objective of this study was to evaluate the incidence of OM in patients on BMT undergoing FBM. 53 patients undergoing treatment received FBMT (red laser, 2J, 20s, 100mW) as a preventive protocol. If MO was observed, an infrared laser (4J, 40s, 100W) was administered. The following data were collected from patients' medical records: sex, age, chemotherapy protocol (QT) and type of BMT. An incidence of 34% was observed in the population studied (20% grade I, 11.3% grade II and 1.9% grade III). Prevention protocols using FBMT significantly reduced the incidence of oral mucositis (p = 0.004). Now, young patients with myeloid leukemia, the time between QT and BMT (p = 0.010) and time of QT (p = 0.018) were directly associated with the increased incidence of oral mucositis. It was concluded that low-intensity preventive laser therapy was associated with a reduction in the incidence of oral mucositis, showing the importance of this therapy in the management of patients undergoing BMT.